Paradoks Ganda Kos Produksi Petani Tembakau (Studi Fenomenologi pada Petani Tembakau di Kabupaten Jember) - Whedy Prasetyo (Jurnal Ekonomi dan Bisnis, 2017)
This study focuses on the dual paradox of production cost phenomenon as a consequence of the tobacco market characteristics. More specifically, we motivate our study by emphasizing the oligopsonic price transaction and farmers’ lack of direct access to factories. The paradox causes production costs to be determined by mediating actors between farmers and tobaccos. More specifically, tengkulak (middlemen) powerfully mediate business transactions between farmers and factories so that price fluctuation harms farmers. Using the phenomenology study, this research harmonizes the production costs determination from the planting time to harvesting time. The production cost harmonization shows that farmers and factories initiate intensive and open communication about their own production costs. It is therefore expected that this practice could eliminate the oligopsonic market and the one-sided price determination by tengkulak who mainly act for cigarette industry. Eventually, it is also expected that the dual paradox of production cost determination could be eliminated.Abstrak Fenomena paradoks ganda kos produksi akibat pasar tembakau merupakan kajian penelitian ini. Kajian ini merujuk akibat transaksi harga yang bersifat oligopsoni dan petani tidak memiliki akses langsung ke pabrik. Paradoks seperti ini membuat kondisi antara petani dan pabrik menentukan beban produksi. Beban produksi yang terjadi akibat proses jual-beli diperantarai oleh tengkulak, sehingga fluktuasi harga tembakau merugikan petani. Penelitian ini mengunakan studi fenomena. Hasil penelitian mewujudkan harmonisasi penentuan kos produksi dari awal masa tanam sampai panen. Harmonisasi kos produksi seperti ini menunjukkan pabrik dan petani membuka wahana komunikasi intensif dan terbuka beban produksi yang harus dikeluarkan masing-masing. Hasil ini diharapkan mengakhir fenomena oligopsoni dan penetapan harga tembakau secara sepihak oleh tengkulak yang menjadi kaki tangan industri rokok. Oleh karena itu, sudah waktunya cerita paradoks ganda penentuan kos produksi diakhiri.